electrode

By adding Ni to the PTC layer of the solid battery electrode, the problem of high heat generation of solid batteries is solved, and the effect of reducing heat generation, improving efficiency and safety is achieved.

CN114628627BActive Publication Date: 2025-02-11TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111481818.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-10
Filing Date
2021-12-07
Publication Date
2025-02-11
Estimated Expiration
2041-12-07

AI Technical Summary

Technical Problem

Existing solid batteries will generate higher heat during use, affecting the efficiency and safety of the equipment.

Method used

A solid battery electrode is designed, using a PTC layer as a key component, which consists of conductive material, Ni and polymer, and the volume ratio of Ni is greater than the volume ratio of conductive material to reduce the heat generation of the battery.

Benefits of technology

By adding Ni to the PTC layer, the heat generation of the solid battery can be effectively reduced and the efficiency and safety of the battery can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114628627B_ABST
    Figure CN114628627B_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode. The object is to provide an electrode capable of reducing the heat generation of a solid battery. The electrode is an electrode for a solid battery, characterized in that the electrode comprises an electrode layer, a current collector, and a PTC layer disposed between the electrode layer and the current collector and in contact with the electrode layer, the PTC layer contains a conductive material, Ni, and a polymer, and the volume ratio of the Ni in the PTC layer is greater than the volume ratio of the conductive material in the PTC layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrode. Background Art

[0002] With the rapid popularization of information-related devices and communication devices such as personal computers, cameras and mobile phones in recent years, the development of batteries used as their power sources has received attention. In addition, the automotive industry is also developing high-output and high-capacity batteries for electric vehicles and hybrid vehicles.

[0003] Among batteries, lithium secondary batteries use lithium, which has the highest ionization tendency among metals, as the negative electrode. Therefore, they have a large potential difference with the positive electrode and can obtain a high output voltage, and therefore have attracted much attention.

[0004] In addition, solid batteries are attracting attention because they use a solid electrolyte as an electrolyte between a positive electrode and a negative electrode instead of an electrolyte solution containing an organic solvent.

[0005] Patent Document 1 discloses an all-solid-state battery having a PTC layer, wherein the PTC layer comprises a polymer, a conductive material, and an insulating inorganic substance.

[0006] Non-Patent Document 1 discloses that when Ni is added to a PTC layer, the melting temperature of the polymer does not change, but the resistance rise temperature decreases.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2019-079611

[0010] Non-patent literature:

[0011] Non-patent document 1: Zhi-Min Dang, et al., Chemical Physics Letters, 438 (2007) 196-202 Summary of the invention

[0012] Problems to be solved by the invention

[0013] In the case of solid-state batteries, heat generation needs to be reduced.

[0014] The present disclosure has been made in view of the above-mentioned actual situation, and its main purpose is to provide an electrode that can reduce the amount of heat generated by a solid battery.

[0015] Means for solving problems

[0016] The electrode disclosed in the present invention is an electrode for a solid battery, characterized in that:

[0017] The electrode comprises an electrode layer, a current collector, and a PTC layer disposed between the electrode layer and the current collector and in contact with the electrode layer.

[0018] The PTC layer contains conductive material, Ni and polymer,

[0019] A volume ratio of the Ni in the PTC layer is greater than a volume ratio of the conductive material in the PTC layer.

[0020] In the electrode of the present disclosure, a volume ratio of the Ni in the PTC layer to the conductive material (Ni / conductive material) may be greater than 1 and 3 or less.

[0021] In the electrode disclosed herein, the volume ratio of the Ni in the PTC layer may be 30 volume % to 35 volume %.

[0022] In the electrode disclosed herein, the average particle size of the Ni particles may be 63 nm to 150 nm.

[0023] Effects of the Invention

[0024] The present disclosure can provide an electrode capable of reducing the amount of heat generated in a solid battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic cross-sectional view showing an example of the solid battery of the present disclosure.

[0026] Figure 2 It is a graph showing the relationship between the resistance of each solid battery of Example 1 and Comparative Example 2 and the temperature.

[0027] Description of Reference Numerals

[0028] 11. Negative electrode collector

[0029] 12 Negative electrode layer

[0030] 13 Solid electrolyte layer

[0031] 14 Positive electrode layer

[0032] 15. Positive electrode collector

[0033] 16 PTC layer

[0034] 100 Solid State Battery DETAILED DESCRIPTION

[0035] The electrode disclosed in the present invention is an electrode for solid batteries, characterized in that the electrode comprises an electrode layer, a current collector and a PTC layer arranged between the electrode layer and the current collector and connected to the electrode layer, the PTC layer contains a conductive material, Ni and a polymer, and the volume proportion of the Ni in the PTC layer is greater than the volume proportion of the conductive material in the PTC layer.

[0036] Here, “PTC” means “Positive Temperature Coefficient”. A “PTC layer” refers to a layer having a property that the resistance changes with a positive coefficient as the temperature rises, that is, a PTC characteristic.

[0037] By adding Ni to the electrode, the battery resistance can be reduced and the PTC function can be developed.

[0038] The electrode disclosed in the present invention includes an electrode layer, a current collector, and a PTC layer disposed between the electrode layer and the current collector and in contact with the electrode layer.

[0039] The electrode disclosed herein may be used as at least one of a positive electrode and a negative electrode, or may be used as both a positive electrode and a negative electrode.

[0040] The electrode layer is a positive electrode layer or a negative electrode layer. Whether the electrode layer is a positive electrode layer or a negative electrode layer can be determined by the type of active material contained in the electrode layer. As for the active material, the same substances as those exemplified in the positive electrode active material and the negative electrode active material described later can be exemplified.

[0041] When the electrode layer is a positive electrode layer, the current collector is a positive electrode current collector, and when the electrode layer is a negative electrode layer, the current collector is a negative electrode current collector.

[0042] The PTC layer in the present disclosure is disposed at least one of between the positive electrode layer and the positive electrode collector and between the negative electrode layer and the negative electrode collector.

[0043] The PTC layer contains conductive material, Ni and polymer.

[0044] The thickness of the PTC layer is not particularly limited and may be 500 nm to 20 μm. The thickness of the PTC layer in the present disclosure is an average thickness and can be measured, for example, by using a film thickness measuring device. In addition, the thickness of the PTC layer can also be measured based on a cross-sectional observation image of the PTC layer using a SEM (scanning electron microscope).

[0045] The volume ratio of Ni in the PTC layer is greater than the volume ratio of the conductive material in the PTC layer.

[0046] When the volume ratio of the conductive material in the PTC layer is set to 1, the volume ratio of Ni in the PTC layer is greater than 1, and may be less than 5, or less than 3. That is, the volume ratio of Ni in the PTC layer to the conductive material (Ni / conductive material) is greater than 1, and may be less than 5, or less than 3.

[0047] The volume ratio of Ni in the PTC layer may be 20 volume % to 50 volume %, or 30 volume % to 35 volume %.

[0048] The average particle size of the Ni particles may be 20 nm to 200 μm, or 63 nm to 150 nm.

[0049] By combining nickel and a carbon material as a conductive material in the PTC layer, the dielectric constant and resistance of the current collector can be controlled.

[0050] In liquid batteries, nickel dissolves at high potentials (4.3 V or higher), making it difficult to use as a material for the PTC layer. On the other hand, in solid batteries, nickel does not diffuse even at high potentials, so it can be used as a material for the PTC layer.

[0051] As a conductive material, there is no particular limitation as long as it has the desired electronic conductivity, and for example, carbon materials can be cited. As carbon materials, for example, carbon blacks such as furnace black, acetylene black, Ketjen black, thermal black, carbon fibers such as carbon nanotubes and carbon nanofibers, activated carbon, graphite, graphene, fullerene, etc. can be cited, among which the above-mentioned carbon black can be used. This is because the above-mentioned carbon black has the advantage of high electronic conductivity relative to the amount added. The shape of the conductive material is not particularly limited, and for example, a particle shape can be cited. The average primary particle size of the conductive material can be, for example, greater than 20 nm and less than 1 μm. Among them, with respect to the average primary particle size of the conductive material, for example, more than 30 primary particle sizes can be measured based on image analysis using an electron microscope such as SEM (scanning electron microscope), and the value obtained as the arithmetic mean thereof can be adopted.

[0052] The content of the conductive material in the PTC layer is not particularly limited and can be 1 volume % to 15 volume %. This is because, when the content of the conductive material is too little, the conductive path formed is reduced, and the electronic conductivity of the PTC layer may become lower. In addition, when the content of the conductive material is too much, the distance between the conductive materials cannot be extended due to the volume expansion of the polymer, and the increase in resistance may be insufficient.

[0053] As the polymer, there is no particular limitation as long as it is a polymer that can expand in volume when the temperature rises, and for example, thermoplastic resins can be cited. As the thermoplastic resin, for example, polyvinylidene fluoride (PVDF), polypropylene, polyethylene, polyvinyl chloride, polystyrene, acrylonitrile butadiene styrene (ABS) resin, methacrylic resin, polyamide, polyester, polycarbonate, polyacetal, etc. can be cited.

[0054] The melting point of the polymer may be higher than the temperature at which the battery is normally used, and may be, for example, 80° C. to 300° C., or 100° C. to 250° C. The melting point can be measured, for example, by differential thermal analysis (DTA).

[0055] The content of the polymer in the PTC layer is not particularly limited and can be 30% to 65% by volume. This is because, when the content of the polymer is too low, the distance between the conductive materials cannot be extended due to the volume expansion of the polymer, and the increase in resistance may be insufficient. When the content of the polymer is too high, the conductive path formed by the conductive material is blocked by the polymer, and the electronic conductivity of the PTC layer may be reduced.

[0056] The manufacturing method of the electrode is as follows. Ni, the above-mentioned conductive material and the above-mentioned polymer are mixed with an organic solvent such as N-methylpyrrolidone to form a slurry. The slurry is applied to a current collector, and the slurry is dried and fired to form a PTC layer on the current collector. Then, an electrode layer mixture containing an electrode active material is arranged on the PTC layer to form an electrode layer, and an electrode having a current collector, a PTC layer, and an electrode layer in sequence can be obtained.

[0057] The electrodes may be constrained at a constraining pressure of 50 Nm to 200 Nm.

[0058] The electrode disclosed in the present invention is an electrode for a solid battery.

[0059] Figure 1 It is a schematic cross-sectional view showing an example of the solid battery of the present disclosure.

[0060] like Figure 1 As shown, the solid battery 100 includes a negative electrode collector 11 , a negative electrode layer 12 , a solid electrolyte layer 13 , a positive electrode layer 14 , and a positive electrode collector 15 in this order, and includes a PTC layer 16 between the positive electrode collector 15 and the positive electrode layer 14 .

[0061] [positive electrode]

[0062] The positive electrode includes a positive electrode layer and a positive electrode current collector, and may include a PTC layer between the positive electrode layer and the positive electrode current collector as required. That is, the positive electrode may be the electrode disclosed in the present invention.

[0063] [Positive electrode layer]

[0064] The positive electrode layer contains a positive electrode active material, and may contain a solid electrolyte, a conductive material, a binder, and the like as optional components.

[0065] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for a solid battery can be used. In the case where the solid battery is a solid lithium secondary battery, the positive electrode active material may be, for example, metallic lithium (Li), lithium alloys, LiCoO 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi x Co 1-x O 2 (0<x<1), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiMnO 2 , heterogeneous element replacement Li-Mn spinel, lithium titanate, lithium metal phosphate, LiCoN, Li 2 SiO 3 , and Li 4 SiO 4 , transition metal oxides, TiS 2 、Si、SiO 2 , Si alloys and lithium storage metal compounds. Heterogeneous element substituted Li-Mn spinel, such as LiMn 1.5 Ni 0.5 O 4 、LiMn 1.5 Al 0.5 O 4 、LiMn 1.5 Mg 0.5 O 4 、LiMn 1.5 Co 0.5 O 4 、LiMn 1.5 Fe 0.5 O 4 , and LiMn 1.5 Zn 0.5 O 4 Lithium titanate, for example, Li 4 Ti 5 O 12 Lithium phosphate is, for example, LiFePO 4 、LiMnPO 4 、LiCoPO 4 and LiNiPO 4 Etc. Transition metal oxides such as V 2 O5 and MoO 3 The lithium storage metal compound is, for example, Mg 2 Sn、Mg 2 Ge、Mg 2 Sb and Cu 3 Sb et al.

[0066] Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and alloys with at least one metal selected from Sn, Ge, and Al.

[0067] The shape of the positive electrode active material is not particularly limited, and may be in the form of particles. When the positive electrode active material is in the form of particles, the positive electrode active material may be a primary particle or a secondary particle. The average particle size (D50) of the positive electrode active material may be, for example, greater than 1 nm and less than 100 μm, or may be greater than 10 nm and less than 30 μm.

[0068] A coating layer containing a Li ion conductive oxide may be formed on the surface of the positive electrode active material because the reaction between the positive electrode active material and the solid electrolyte can be suppressed.

[0069] Examples of the Li ion conductive oxide include LiNbO 3 , Li 4 Ti 5 O 12 and Li 3 PO 4 The thickness of the coating is, for example, 0.1 nm or more, and may be 1 nm or more. On the other hand, the thickness of the coating is, for example, 100 nm or less, and may be 20 nm or less. The coverage of the coating on the surface of the positive electrode active material is, for example, 70% or more, and may be 90% or more.

[0070] As the solid electrolyte, the same solid electrolytes as those exemplified in the solid electrolyte layer can be exemplified.

[0071] The content of the solid electrolyte in the positive electrode layer is not particularly limited, and can be, for example, in the range of 1% by mass to 80% by mass when the total mass of the positive electrode layer is 100% by mass.

[0072] As the conductive material, known materials can be used, for example, carbon materials and metal particles can be mentioned. As the carbon material, at least one selected from acetylene black, furnace black, VGCF, carbon nanotubes and carbon nanofibers can be mentioned. Wherein, from the viewpoint of electronic conductivity, it can be at least one selected from VGCF, carbon nanotubes and carbon nanofibers. As the metal particles, particles such as Ni, Cu, Fe and SUS can be mentioned.

[0073] The content of the conductive material in the positive electrode layer is not particularly limited.

[0074] Examples of the binder (adhesive) include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.

[0075] The thickness of the positive electrode layer is not particularly limited.

[0076] The positive electrode layer can be formed by a conventionally known method.

[0077] For example, a positive electrode active material and other components as needed are added to a solvent and stirred to prepare a positive electrode layer slurry, which is then applied onto one side of a support such as a positive electrode current collector and dried to obtain a positive electrode layer.

[0078] Examples of the solvent include butyl acetate, butyl butyrate, heptane, and N-methyl-2-pyrrolidone (NMP).

[0079] The method for coating the positive electrode layer slurry on one side of a support such as a positive electrode collector is not particularly limited, and examples thereof include doctor blade method, metal mask printing method, electrostatic coating method, dip coating method, spraying method, roll coating method, gravure coating method and screen printing method.

[0080] As the support, any self-supporting support may be appropriately selected and used without particular limitation, and for example, metal foil of Cu, Al, or the like may be used.

[0081] In addition, as another method for forming the positive electrode layer, the positive electrode layer can also be formed by press-molding the powder of the positive electrode mixture containing the positive electrode active material and other components as needed. When the powder of the positive electrode mixture is press-molded, a pressing pressure of about 1 MPa or more and about 600 MPa or less is usually applied.

[0082] The pressurizing method is not particularly limited, and examples thereof include a method of applying pressure using a flat plate press, a roll press, and the like.

[0083] [Positive electrode collector]

[0084] As the positive electrode current collector, a known metal that can be used as a current collector for a solid battery can be used. As such a metal, a metal material containing one or more elements selected from Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge and In can be exemplified. As the positive electrode current collector, for example, SUS, aluminum, nickel, iron, titanium and carbon can be cited.

[0085] The form of the positive electrode current collector is not particularly limited, and various forms such as foil and mesh may be adopted. The thickness of the positive electrode current collector varies depending on the shape, and may be, for example, in the range of 1 μm to 50 μm or in the range of 5 μm to 20 μm.

[0086] [negative electrode]

[0087] The negative electrode includes a negative electrode current collector and a negative electrode layer, and may include a PTC layer between the negative electrode layer and the negative electrode current collector as required. That is, the negative electrode may also be the electrode disclosed in the present invention.

[0088] [Negative electrode layer]

[0089] The negative electrode layer contains at least a negative electrode active material and, if necessary, contains a conductive material, a binder, a solid electrolyte, and the like.

[0090] Examples of the negative electrode active material include graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, soft carbon, lithium single substance, lithium alloy, Si single substance, Si alloy, and Li 4 Ti 5 O 12 As the lithium alloy and the Si alloy, the same materials as those exemplified in the positive electrode active material can be used.

[0091] There is no particular limitation on the shape of the negative electrode active material, and examples thereof include particle-shaped and plate-shaped. When the negative electrode active material is in particle-shaped, the negative electrode active material may be a primary particle or a secondary particle. In addition, the average particle size (D50) of the negative electrode active material may be, for example, greater than 1 nm and less than 100 μm, or greater than 10 nm and less than 30 μm.

[0092] The shape of the negative electrode active material is not particularly limited, and examples thereof include a particle shape and a plate shape.

[0093] The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer.

[0094] The thickness of the negative electrode layer is not particularly limited, and may be, for example, 10 to 100 μm.

[0095] The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass.

[0096] [Negative electrode current collector]

[0097] The material of the negative electrode current collector can be a material that does not alloy with Li, for example, SUS, copper and nickel. As the form of the negative electrode current collector, for example, foil and plate can be mentioned. The top view shape (planar shape) of the negative electrode current collector is not particularly limited, for example, a circle, an ellipse, a rectangle, and any polygon can be mentioned. In addition, the thickness of the negative electrode current collector varies depending on the shape, for example, it can be in the range of 1 μm to 50 μm, and it can also be in the range of 5 μm to 20 μm.

[0098] [Solid electrolyte layer]

[0099] The solid electrolyte layer contains at least a solid electrolyte.

[0100] As the solid electrolyte contained in the solid electrolyte layer, a known solid electrolyte that can be used for a solid battery can be appropriately used, and oxide solid electrolytes and sulfide solid electrolytes can be mentioned. In the present disclosure, a sulfide solid electrolyte can be used as a solid electrolyte. Sulfide solid electrolytes have high ion conductivity, but may generate hydrogen sulfide due to temperature rise. Therefore, by using a PTC layer to increase resistance and effectively suppress temperature rise, a solid battery that suppresses the generation of hydrogen sulfide and has high ion conductivity can be made.

[0101] Examples of the sulfide solid electrolyte include Li 2 SP 2 S 5 , Li 2 S-SiS 2 、LiX-Li 2 S-SiS 2 、LiX-Li 2 SP 2 S 5 、LiX-Li 2 O-Li 2 SP 2 S 5 、LiX-Li 2 SP 2 O 5 、LiX-Li 3 PO 4 -P 2 S 5 and Li 3 PS 4 Etc. It should be noted that the above “Li 2 SP2 S 5 " refers to the use of Li 2 S and P 2 S 5 The material formed by the raw material combination, and the other records are the same.

[0102] In addition, "X" in the above-mentioned LiX represents a halogen element. In the raw material composition containing the above-mentioned LiX, LiX may contain one or more kinds. When containing two or more kinds of LiX, the mixing ratio of the two or more kinds is not particularly limited.

[0103] The molar ratio of each element in the sulfide solid electrolyte can be controlled by adjusting the content of each element in the raw material. In addition, the molar ratio and composition of each element in the sulfide solid electrolyte can be measured by, for example, ICP emission spectrometry.

[0104] The sulfide solid electrolyte may be sulfide glass, crystallized sulfide glass (glass ceramic), or a crystalline material obtained by subjecting a raw material composition to a solid phase reaction treatment.

[0105] The crystal state of the sulfide solid electrolyte can be confirmed by, for example, performing powder X-ray diffraction measurement of the sulfide solid electrolyte using CuKα rays.

[0106] Sulfide glass can be prepared by adjusting the raw material composition (e.g. Li 2 S and P 2 S 5 The amorphous treatment may include, for example, mechanical grinding.

[0107] Glass ceramics can be obtained, for example, by heat treating sulfide glass.

[0108] The heat treatment temperature may be a temperature higher than the crystallization temperature (Tc) observed by thermal analysis of the sulfide glass, and is usually 195° C. or higher. On the other hand, the upper limit of the heat treatment temperature is not particularly limited.

[0109] The crystallization temperature (Tc) of sulfide glass can be measured by differential thermal analysis (DTA).

[0110] The heat treatment time is not particularly limited as long as it is a time that can obtain the desired crystallinity of the glass ceramic, and is, for example, in the range of 1 minute to 24 hours, particularly in the range of 1 minute to 10 hours.

[0111] The method of heat treatment is not particularly limited, and an example thereof includes a method using a calcining furnace.

[0112] As the oxide solid electrolyte, for example, a substance having a garnet-type crystal structure containing Li element, La element, A element (A is at least one of Zr, Nb, Ta and Al) and O element can be cited. As the oxide solid electrolyte, for example, Li 3+x PO 4-x N x (1≤x≤3) etc.

[0113] From the viewpoint of good handleability, the solid electrolyte may be in the form of particles.

[0114] The average particle size (D50) of the solid electrolyte particles is not particularly limited, but the lower limit may be 0.5 μm or more and the upper limit may be 2 μm or less.

[0115] In the present disclosure, unless otherwise specified, the average particle size of particles is the value of the volume-based median particle size (D50) measured by laser diffraction scattering particle size distribution measurement. In addition, in the present disclosure, the median particle size (D50) refers to the diameter (volume average diameter) when the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.

[0116] The solid electrolyte may be used alone or in combination of two or more. In addition, when two or more solid electrolytes are used, two or more solid electrolytes may be mixed, or two or more layers of solid electrolytes may be formed to form a multilayer structure.

[0117] The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, and may be, for example, 50% by mass or more, 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, or 100% by mass.

[0118] From the viewpoint of showing plasticity, etc., the solid electrolyte layer may also contain a binder. As such a binder, materials exemplified as binders used in the positive electrode layer, etc. may be exemplified. However, from the viewpoint of easily achieving high output, in order to form a solid electrolyte layer that prevents excessive aggregation of solid electrolytes and has uniformly dispersed solid electrolytes, etc., the binder contained in the solid electrolyte layer may be set to less than 5% by mass.

[0119] The thickness of the solid electrolyte layer is not particularly limited, but is usually 0.1 μm or more and 1 mm or less.

[0120] As a method for forming a solid electrolyte layer, there is a method of pressure-molding a powder of a solid electrolyte material containing a solid electrolyte, etc. When the powder of the solid electrolyte material is pressure-molded, a pressing pressure of about 1 MPa to 600 MPa is usually applied.

[0121] The pressurizing method is not particularly limited, and the pressurizing methods exemplified in the formation of the positive electrode layer may be mentioned.

[0122] The solid battery includes an outer casing and a restraining member for accommodating a stacked body including a positive electrode collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode collector in this order, as required.

[0123] The material of the outer casing is not particularly limited as long as it is a material stable to the electrolyte, and examples thereof include resins such as polypropylene, polyethylene, and acrylic resin.

[0124] As for the restraining member, any known restraining member that can be used as a restraining member for solid batteries can be used as long as it can apply restraining pressure in the stacking direction to the stack. For example, a restraining member having a plate-like portion that clamps the two surfaces of the stack, a rod-like portion that connects the two plate-like portions, and an adjusting portion that is connected to the rod-like portion and adjusts the restraining pressure through a threaded structure or the like can be cited. The desired restraining pressure can be applied to the stack by the adjusting portion.

[0125] The restraining pressure is not particularly limited, and for example, it may be 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. This is because increasing the restraining pressure has the advantage of making it easier for each layer to come into good contact. On the other hand, the restraining pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less. This is because when the restraining pressure is too large, the restraining component is required to have high rigidity, and the size of the restraining component may become larger.

[0126] The solid battery may include only one of the above-mentioned stacked bodies, or may be a battery formed by stacking a plurality of stacked bodies.

[0127] The solid battery may be a primary battery or a secondary battery, and the secondary battery may be a secondary battery. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful as a vehicle battery, for example. In addition, the solid battery may be a solid lithium secondary battery.

[0128] Examples of the shape of the solid battery include a coin shape, a laminate shape, a cylindrical shape, and a square shape.

[0129] As for the manufacturing method of the solid battery disclosed in the present invention, for example, a solid electrolyte layer is first formed by press-molding the powder of the solid electrolyte material. Then, the positive electrode layer is obtained by press-molding the powder of the positive electrode mixture containing the positive electrode active material on one side of the solid electrolyte layer. Then, the negative electrode layer is obtained by press-molding the powder of the negative electrode material on one side of the negative electrode collector. On the surface of the solid electrolyte layer opposite to the surface on which the positive electrode layer is formed, a stack of the negative electrode collector-negative electrode layer is installed in such a way that the negative electrode layer is in contact with the solid electrolyte layer. Then, a PTC layer is formed on the positive electrode collector. Then, the positive electrode collector is installed in such a way that the PCT layer is in contact with the surface of the positive electrode layer on the side opposite to the solid electrolyte layer. The solid battery disclosed in the present invention is also manufactured in this way.

[0130] At this time, the pressing pressure when the powder of the negative electrode material, the powder of the solid electrolyte material, and the powder of the positive electrode mixture are press-molded is usually about 1 MPa or more and 600 MPa or less.

[0131] The pressurizing method is not particularly limited, and the pressurizing methods exemplified in the formation of the positive electrode layer may be mentioned.

[0132] Example

[0133] [Production of negative electrode]

[0134] Prepare negative electrode active material (Si particles, average particle size 0.5 μm), sulfide solid electrolyte (10LiI-15LiBr-75 (0.75Li 2 S-0.25P 2 S 5 ) (mol%), average particle size 0.5 μm), conductive material (VGCF-H) and binder (SBR).

[0135] The negative electrode active material: sulfide solid electrolyte: conductive material: binder were weighed at a mass ratio of 47.0:44.6:7.0:1.4 and mixed with a dispersion medium (diisobutyl ketone). The obtained mixture was dispersed with an ultrasonic homogenizer (UH-50, manufactured by E-SEM Technology Co., Ltd.) to obtain a negative electrode slurry.

[0136] The obtained negative electrode slurry was applied to a negative electrode collector (Ni foil, thickness 22 μm) by a doctor blade method using an applicator, and dried at 100°C for 30 minutes to obtain a negative electrode having a negative electrode layer on the negative electrode collector. Then, the opposite side of the negative electrode collector was similarly coated to obtain a double-sided negative electrode structure having negative electrode layers on both sides of the negative electrode collector. The thickness of each negative electrode layer was 60 μm.

[0137] [Production of positive electrode layer]

[0138] LiNbO was prepared by using a tumble flow granulation coating device. 3 The coated positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 O 2 , average particle size 10μm), sulfide solid electrolyte (10LiI-15LiBr-75 (0.75Li 2 S-0.25P 2 S 5 ) (mol%), average particle size 0.5 μm), conductive material (VGCF-H) and binder (SBR).

[0139] The mixture was weighed in a mass ratio of positive electrode active material: sulfide solid electrolyte: conductive material: binder = 83.3:14.4:2.1:0.2, and mixed with a dispersion medium (diisobutyl ketone).

[0140] The obtained mixture was dispersed with an ultrasonic homogenizer (UH-50, manufactured by Esu-Emute Co., Ltd.) to obtain a positive electrode slurry. The obtained positive electrode slurry was applied to a support (aluminum foil (thickness 15 μm)) by a doctor blade method using an applicator, and dried at 100° C. for 30 minutes to form a positive electrode layer on the support to obtain a positive electrode layer-Al foil.

[0141] The thickness of the positive electrode layer was 100 μm.

[0142] [Fabrication of Solid Electrolyte Layer]

[0143] The sulfide solid electrolyte (10LiI·15LiBr·75(0.75Li 2 S·0.25P 2 S 5 ) (mol%), average particle size 2.0 μm) and binder (SBR) are weighed and mixed with a dispersion medium (diisobutyl ketone). The obtained mixture is dispersed with an ultrasonic homogenizer (UH-50, manufactured by Esumete Co., Ltd.) to obtain a solid electrolyte layer slurry. The obtained solid electrolyte layer slurry is applied to an Al foil (thickness 15 μm) by a doctor blade method using an applicator, and dried at 100°C for 30 minutes to obtain a solid electrolyte layer on the Al foil. The thickness of the solid electrolyte layer is 30 μm.

[0144] (Example 1)

[0145] [Production of Ni-containing PTC layer]

[0146] Carbon black (manufactured by Tokai Carbon Co., Ltd.) with an average primary particle size of 20 nm as a conductive material, PVDF (KF polymer L#9130 manufactured by Kuraha Co., Ltd.) as a polymer, and Ni particles (average particle size 63 nm) were mixed with NMP as a dispersion medium at a volume ratio of 10:60:30 to prepare a paste. That is, the volume ratio of Ni to the conductive material was made to be conductive material: Ni = 1:3. The prepared paste was applied to an aluminum foil (1N30 manufactured by UACJ Co., Ltd.) with a thickness of 15 μm as a collector so that the thickness after drying was 5 μm, dried at 60°C for 10 minutes, and then dried in a drying furnace at 100°C for 1 hour to obtain a collector-PTC layer.

[0147] [Production of solid state batteries]

[0148] The layer area is 7.2×7.2cm 2 The double-sided negative electrode structure cut out in the manner of 7.2×7.2cm 2 The solid electrolyte layer-Al foil cut out in the manner of the negative electrode structure was laminated in such a way that one negative electrode layer in the negative electrode structure was in direct contact with the solid electrolyte layer, and then pressed at 1.6 t / cm, and then the Al foil was peeled off from the solid electrolyte layer. 2 The positive electrode layer-Al foil cut out in a manner is laminated in a manner that the positive electrode layer is in direct contact with the solid electrolyte layer, and is pressed at 1.6 t / cm. Then, the Al foil is peeled off from the positive electrode layer and further pressed at 5 t / cm. Then, the collector-PTC layer is laminated on the surface of the positive electrode layer on the opposite side of the solid electrolyte layer in a manner that the positive electrode layer is in direct contact with the PTC layer. The solid electrolyte layer, positive electrode layer, PTC layer, and positive electrode collector are also laminated on the other negative electrode layer of the double-sided negative electrode structure in the same manner as described above. Thus, an electrode stack having a positive electrode collector, a PTC layer, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, a negative electrode collector, a negative electrode layer, a solid electrolyte layer, a positive electrode layer, a PTC layer, and a positive electrode collector in sequence is obtained. After welding the terminals of the obtained electrode stack, a laminated battery is formed (laminate) to produce a solid battery.

[0149] (Example 2)

[0150] A PTC layer was produced in the same manner as in Example 1 except that Ni particles having an average particle size of 150 nm were used. Then, a solid battery was produced in the same manner as in Example 1.

[0151] (Comparative Example 1)

[0152] In the above-mentioned [Preparation of Ni-containing PTC layer], carbon black (manufactured by Tokai Carbon Co., Ltd.) with an average primary particle size of 20 nm as a conductive material, PVDF (KF polymer L#9130 manufactured by Kuraha Corporation) as a polymer, and Ni particles (average particle size 150 nm) were mixed with NMP as a dispersion medium at a volume ratio of 10:80:10 to prepare a paste, and the PTC layer was prepared by the same method as in Example 1. That is, the volume ratio of Ni to the conductive material was made to be conductive material:Ni=1:1. Then, a solid battery was prepared by the same method as in Example 1.

[0153] (Comparative Example 2)

[0154] In the above-mentioned [Preparation of Ni-containing PTC layer], Ni particles were not used, and carbon black (manufactured by Tokai Carbon Co., Ltd.) with an average primary particle size of 20 nm as a conductive material and PVDF (KF polymer L#9130 manufactured by Kuraha Corporation) as a polymer were mixed with NMP as a dispersion medium at a volume ratio of 10:90. The PTC layer was prepared in the same manner as in Example 1. Then, a solid battery was prepared in the same manner as in Example 1.

[0155] (Comparative Example 3)

[0156] A carbon-coated aluminum foil was prepared as a current collector without making a Ni-containing PTC layer. Then, the current collector was used as a positive electrode current collector, and a solid battery was prepared by sequentially configuring the following: positive electrode current collector, positive electrode layer, solid electrolyte layer, negative electrode layer, negative electrode current collector, negative electrode layer, solid electrolyte layer, positive electrode layer, positive electrode current collector. The thickness of the carbon coating was 4 μm.

[0157] [Evaluation method]

[0158] The solid batteries of Examples 1 to 2 and Comparative Examples 1 to 3 were evaluated by performing the nail penetration test and the charge and discharge test described below.

[0159] [Charge and discharge test]

[0160] Each solid battery obtained in Examples 1 to 2 and Comparative Examples 1 to 3 was dimensionally constrained at a constraining pressure of 5 MPa, and charged to 4.05 V by constant current-constant voltage (CC-CV) at 0.0194 A. Then, CC-CV discharge was performed at 0.0194 A to 3.0 V. Then, each solid battery was charged again. The charging at this time was regarded as the initial charging.

[0161] [Nail penetration test]

[0162] Each of the solid batteries of Examples 1 to 2 and Comparative Examples 1 to 3 was charged at a constant current of 1 / 3C to 4.05 V, and then charged at a constant voltage of 4.05 V and 20 A.

[0163] Then, at room temperature (25℃±5℃) and 4.05V constant voltage charging, a nail with a diameter of 3.0mm and a tip angle of 30 degrees was used to pierce the side of the solid battery at a speed of 0.1mm / sec to cause an internal short circuit. The sneak current at this time was calculated to find the heat generated by the solid battery. The results are shown in Table 1.

[0164] The conditions of the nail penetration test are as follows.

[0165] Nail speed: 0.1mm / sec

[0166] Constraint pressure: 5MPa

[0167] Applied current: 20A (max setting)

[0168] Temperature: Room temperature (25℃±5℃)

[0169] Nail penetration depth: 0.4-0.8mm from the positive electrode contact position

[0170] Pin: French embroidery needle No. 3

[0171] [Table 1]

[0172]

[0173] [Evaluation results]

[0174] Compared with Comparative Examples 1 to 3, Examples 1 to 2 have lower calorific value.

[0175] Figure 2 It is a graph showing the relationship between the resistance of each solid battery of Example 1 and Comparative Example 2 and the temperature.

[0176] like Figure 2 As shown, the solid battery of Example 1 has an increase in resistance at a lower temperature than the solid battery of Comparative Example 2.

Claims

1. An electrode for a solid battery, characterized in that: The electrode comprises an electrode layer, a current collector, and a PTC layer disposed between the electrode layer and the current collector and in contact with the electrode layer. The PTC layer contains conductive material, Ni and polymer, The conductive material is a carbon material, the polymer is a thermoplastic resin, The volume ratio of the conductive material in the PTC layer is 10 volume % to 15 volume %, and the volume ratio of Ni in the PTC layer is 30 volume % to 35 volume %.

2. The electrode according to claim 1, wherein The volume ratio of the Ni in the PTC layer to the conductive material, ie, Ni / conductive material, is 3.

3. The electrode according to claim 1 or 2, wherein The volume ratio of the conductive material in the PTC layer is 10 volume %, and the volume ratio of Ni in the PTC layer is 30 volume %.

4. The electrode according to claim 1 or 2, wherein The average particle size of the Ni particles is 63nm~150nm.

Citation Information

Patent Citations

  • All-solid battery

    JP2019079611A

  • All-solid-state battery

    CN106981664A

  • PTC-device with improved antioxidant and secondary battery using the same

    KR1020080107142A